2010
DOI: 10.1007/s10295-010-0818-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival of commercial yeasts in the winery environment and their prevalence during spontaneous fermentations

Abstract: Inoculation of active dry yeasts during the wine-making process has become a common practice in most wine-producing regions; this practice may affect the diversity of the indigenous population of Saccharomyces cerevisiae in the winery. The aim of this work was to study the incidence of commercial yeasts in the experimental winery of Estación de Viticultura e Enoloxía de Galicia (EVEGA) and their ability to lead spontaneous fermentations. To do this, 64 spontaneous fermentations were carried out in the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 18 publications
1
35
0
9
Order By: Relevance
“…Hanseniaspora has also been previously reported to colonize winery surfaces [3] and plays an important role in the early stages of wine fermentation [13]. While this yeast is typically present on grapes [17], winery surface establishment may ensure that the same strains are introduced to successive batches and vintages of wine as previously shown for Saccharomyces [19], [20], [21], possibly supporting the reproducibility, as well as regionality, of wine sensory characteristics produced at a given facility. Another yeast detected at lower levels on winery surfaces prior to harvest was Candida zemplinina (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Hanseniaspora has also been previously reported to colonize winery surfaces [3] and plays an important role in the early stages of wine fermentation [13]. While this yeast is typically present on grapes [17], winery surface establishment may ensure that the same strains are introduced to successive batches and vintages of wine as previously shown for Saccharomyces [19], [20], [21], possibly supporting the reproducibility, as well as regionality, of wine sensory characteristics produced at a given facility. Another yeast detected at lower levels on winery surfaces prior to harvest was Candida zemplinina (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Bathed with the nutritious medium of grape juice on a seasonal basis, these surfaces become very promising sites for microbial adsorption and biofilm production, potentially leading to continuous shedding of microbes into successive batches of wine. Specific Saccharomyces strains can become established on winery surfaces, resulting in repeatable detection over multiple years in uninoculated wines [19], [20], [21], [22]. The distribution of non- Saccharomyces fungi on specific winery surfaces has been studied to a limited extent at isolated timepoints using culture-based techniques [2], [3], [23].…”
Section: Introductionmentioning
confidence: 99%
“…This may occur by any number of vectors, but humans, insects and birds seem likely candidates, and the two former have been previously implicated (Goddard et al, 2010). The observation that a diverse natural population of S. cerevisiae contributed to these spontaneous ferments is another piece of evidence again showing that spontaneous ferments are not driven by 'escaped' commercial isolates (Blanco et al, 2011), even in large commercial wineries that also run parallel inoculated ferments (as was the case here), but driven by a diversity of natural isolates.…”
Section: Discussionmentioning
confidence: 93%
“…Analyses of the yeast populations found on winery surfaces, equipment, and in winery air have also been conducted (Blanco, Orriois, & Losada, 2011;Ciani, Mannazzu, Maringeli, Clemente, & Martini, 2004;Garijo et al, 2008;Garijo et al, 2009;González-Arenzana, Santamaria, López, Tenorio, & López-Alfaro, 2012;Haas et al, 2010;Martini, 2003;Mercado et al, 2004;Ocón, Gutiérrez, Garijo, López, & Santamaria, 2010;Ocón et al, 2013;Renouf et al, 2007;Santamaria, López, López, Garijo, & Gutiérrez, 2008). These studies have demonstrated the role that the winery microbiota are a significant source of pre-fermentation microbial activity in juice and must (Fleet & Heard, 1993;Renouf et al, 2007).…”
Section: Pre-fermentation Microbiotamentioning
confidence: 99%